Impact of Nonlinear Power Amplifier on Orthogonal Time Sequency Multiplexing - Sangeeta N.; Sharma S.; Deka K.; Sarawadekar K.P. (My University, 2025)
Two-dimensional orthogonal time sequency multiplexing (OTSM) modulation is considered as a promising technique for time and frequency selective channels, unlike conventional orthogonal frequency division multiplexing (OFDM). Paper investigates the effects of nonlinear power amplifiers (NPAs) and phase noise (PN) on the OTSM system's bit error rate (BER) performance over the Extended Vehicular A model (EVA) channel. The analysis considers the BER performance concerning input-back-off (IBO) levels and the nonlinearity parameters of the NPA. The findings reveal that both NPAs and PN substantially degrades OTSM performance, particularly with higher modulation schemes and lower IBO values. Additionally, we numerically explore how variations in system parameters affect BER performance. © 2024 IEEE.